On the Poisson representation of a function harmonic in the upper half-plane - Gergün, Seçil; Ostrovskii, I. V. (Математическая физика, анализ, геометрия, 2002)
New conditions of validity of the Poisson representation (in usual and generalized form) for a function harmonic in the upper half-plane are obtained. These conditions differ from known ones by weaker growth restrictions inside the half-plane and stronger restrictions on the behavior in the neighbourhood of the real axis.